Proceedings 2014 Workshop on Usable Security 2014
DOI: 10.14722/usec.2014.23037
|View full text |Cite
|
Sign up to set email alerts
|

Introducing Precautionary Behavior by Temporal Diversion of Voter Attention from Casting to Verifying their Vote

Abstract: Most electronic voting systems in use today provide printouts so called voter verifiable paper audit trails (VVPATs). Voters are supposed to verify these before they put them into the ballot box in order to detect election fraud. A number of studies have shown that voters are unlikely to do so when using current systems. Thus, it is very likely that malicious electronic voting systems print the wrong candidates without being detected. We introduce precautionary behavior by providing voters with "just in time" … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2
2
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…Therefore, in the user study we integrated voter verifiability instructions, which we have developed by Budurushi et. al [12]. The verifiability instructions and their integration in the vote casting process are presented in Figure 3.…”
Section: Instructions For Votersmentioning
confidence: 99%
“…Therefore, in the user study we integrated voter verifiability instructions, which we have developed by Budurushi et. al [12]. The verifiability instructions and their integration in the vote casting process are presented in Figure 3.…”
Section: Instructions For Votersmentioning
confidence: 99%
“…Post-questionnaire. This questionnaire serves to compare the results of our study with the results presented by Budurushi et al [11]. Thus, we compare participants' self-reported answers and their actual behaviour with respect to verifying their printed ballot.…”
Section: Questionnairesmentioning
confidence: 85%
“…The treatment group was provided with the stimulus proposed by Budurushi et al [11]: pre-printed verification instructions on the reverse of the printed ballot. The control group was provided with a printed ballot with nothing printed on the reverse.…”
Section: Experimental Setup Design and Proceduresmentioning
confidence: 99%
“…The idea is that the server detects the browser being used and displays the corresponding instructions. 7 Note that we are not implying that the any of these institutes have agreed to provide such a service. This proposed amelioration approach removes the need for manual recording and should thus ease the verification process.…”
Section: "Cast As Intended" Verificationmentioning
confidence: 94%
“…Similar conclusions were drawn by Herrnson et al [14] based on the times participants spend examining the printouts. Recently, Budurushi et al [7] reported a promising finding. The authors found that the number of voters verifying plain text VV-PATs increases significantly, if voters are confronted with pre-printed "just-in-time" verification instructions.…”
Section: Related Workmentioning
confidence: 97%